RESPON PERTUMBUHAN TANAMAN LADA (Piper nigrum L.) DAN PUPUK KOMPOS: Response to The Growth of Pepper Plant and Compost Fertilizer - Elvi Laula; Andi Rusdayani Amin; Abd Haris Bahrun (Program Studi Agroteknologi Fakultas Pertanian, Peternakan, dan Kehutanan Universitas Muslim Maros, 2018)
This research is aimed to understand the vegetative growth of pepper plant by giving azotobacter and compos. This research was conducted from June to September in 2017. The form of this research was a trial by using two factors of randomized group design. Azotobacter as the first factor consists of 4 levels: 0,40 x 108 CFU, 60 x 108 CFU, and 80 x 108 CFU and compos fertilizer consists of 3 levels: 2,5 kg.plant-1, 5 kg.plant-1 and 7,5 kg.plant-1. The result of this research showed that azotobacter 60 x 108 UFU contributed to the growth of tendril (48,42 cm), the number of segments (29), index chlorophyll of leaf (135069,75), number of stomata (15,97) and the density of stomata (37,62 stomata.mm-2). Compos fertilizer 7,5 kg.plant-1 contributed to the growth of tendril (48,42 cm), the index of the segment of the leaf (56,35) and index of the chlorophyll of the leaf (135069,75). The interaction treatment of azotobacter 60 x 108 CFU with compos fertilizer 7,5 kg.plant-1 has the highest index (135069,75)